2017
DOI: 10.1007/s10068-017-0297-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbial safety and quality changes of brown and white cooked rice treated with atmospheric pressure plasma

Abstract: The microbial and physicochemical properties of brown and white cooked rice treated by atmospheric pressure plasma (APP). APP was produced (250 W, 15 kHz, ambient air) and applied to brown and white cooked rice for 5, 10, and 20 min. The 20-min plasma treatment reduced in bacterial counts by 2.01 log CFU/g when cooked rice were inoculated with or O157:H7. The pH of the brown cooked rice was decreased by the 5-min plasma. The hardness values of APP-treated brown and white cooked rice were lower than untreated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 26 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…These adverse effects were reported in meat products such as pork, beef, chicken, seafood, and sushi (Kulawik et al., 2018) whereby increased in the peroxide value and 2‐thiobarbituric acid reactive substances (TBRS) were observed. Similar oxidation has been noticed in cereal products including white rice, brown rice, and wheat flour (Lee et al., 2018). Therefore, all these applications involving CAP technology needs to be optimized for treating any food products with high lipid substance (Gavahian et al., 2018).…”
Section: Advantages and Disadvantages Of Capsupporting
confidence: 73%
“…These adverse effects were reported in meat products such as pork, beef, chicken, seafood, and sushi (Kulawik et al., 2018) whereby increased in the peroxide value and 2‐thiobarbituric acid reactive substances (TBRS) were observed. Similar oxidation has been noticed in cereal products including white rice, brown rice, and wheat flour (Lee et al., 2018). Therefore, all these applications involving CAP technology needs to be optimized for treating any food products with high lipid substance (Gavahian et al., 2018).…”
Section: Advantages and Disadvantages Of Capsupporting
confidence: 73%
“…The PEF inactivates the enzymes by changing their secondary, tertiary, and quaternary structures (Qian, Gu, Jiang, & Chen, ). In other studies, cold atmospheric plasma treatments protected BR against growth of microorganisms during storage (Lee, Kim, Woo et al., , ; Suhem, Matan, Nisoa, & Matan, ). Also, plasma treatment reduced the cooking time, fat acidity, and the activity of α‐amylase and lipoxygenase of BR during storage (Chen, Hung, Lin, & Liou, ).…”
Section: Preservation Technologiesmentioning
confidence: 83%
“…However, the lipid oxidation of cooked and plasma treated BR and WR samples was greater than that of plasma untreated samples. The enhanced lipid oxidation of the plasma treated rice may be attributed to radicals and reactive oxygen species produced by plasma‐induced oxidative stress (Lee et al., ). The influence of plasma treatment may vary depend on the amount of plasma or voltage and treatment time.…”
Section: Preservation Technologiesmentioning
confidence: 99%
“…Lipid oxidation and increased rancidity have been previously reported, depending on the matrix and plasma conditions applied (Gavahian et al, 2018;Lee et al, 2018;Pérez-Andrés et al, 2020). According to Gebremical et al (2019), an increase of FFA in peanuts was observed with a power of 36 W in a DBD plasma.…”
Section: Quantification Of Free Fatty Acidsmentioning
confidence: 89%